2017
DOI: 10.18203/issn.2454-5929.ijohns20174207
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and pattern of thyroid malignancy in thyroid nodule in Aseer Central Hospital in KSA

Abstract: <p class="abstract"><strong>Background:</strong> <span lang="EN-IN">Thyroid nodules are common in the general population, especially in women. Non palpable nodules are often found when patients undergo diagnostic imaging such as ultrasonogra­phy and computed tomography of the chest and neck. This retrospective study to assess the Prevalence of thyroid malignancy in thyroid nodule related to gender, age, and pathology, in Aseer Central Hospital KSA. </span></p><p class="ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
2
1
Order By: Relevance
“…There was notable female predilection in this study which was seemingly following existing literature. 7,11,12 In contrast to earlier findings of colloid goiter as the most common pre-operative FNAC finding, we did not replicate similar observations. Current study found out that majority of lesion were preoperatively diagnosed as papillary carcinoma (42%), however, this doesn't imply that majority of lesion pre-operatively were malignant in nature.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…There was notable female predilection in this study which was seemingly following existing literature. 7,11,12 In contrast to earlier findings of colloid goiter as the most common pre-operative FNAC finding, we did not replicate similar observations. Current study found out that majority of lesion were preoperatively diagnosed as papillary carcinoma (42%), however, this doesn't imply that majority of lesion pre-operatively were malignant in nature.…”
Section: Discussioncontrasting
confidence: 99%
“…9,10 The mean age of patients recruited in this study was similar to Pradhan et al 9 Most subjects recruited in the current study presenting with thyroid nodules were in the fifth decade, which did not corroborate previous studies. 5,7,11 Only patients with multinodular goiter were included in similar studies conducted in Nepal. 5,7 Majority of females in the current study fell into the age group 21-30 years and did not follow the finding of Shrestha et al 4 We observed similar discordance in the distribution of males according to age group.…”
Section: Discussionmentioning
confidence: 99%
“…3 Most of the thyroid disorders are benign in nature and thyroid enlargements are seen more common in females than in males. 4 Thyroid gland disorders usually manifests as enlargement of the thyroid gland (goiters) or as variations in hormone levels or as both. Around 4%-5% of the population present with clinically as externally visible nodules of the thyroid.…”
Section: B a C K G R O U N Dmentioning
confidence: 99%